(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Substance use disorder (SUD) negatively affects individuals’ physical, psychological, and social well-being. While rehabilitation programs primarily focus on medical and psychological interventions, the role of physical and occupational therapy in enhancing functional recovery, pain management, and mental health remains underexplored. This study examines the impact of therapy duration on functional independence, pain reduction, and depression levels among individuals undergoing rehabilitation in Karachi, Pakistan. Methods: A total of 100 patients from an anti-narcotics rehabilitation center participated in the study. Functional status, pain levels, and depression were assessed using the Functional Independence Measure (FIM), Visual Analog Scale (VAS), and Beck Depression Inventory (BDI), respectively. Pearson’s correlation analysis and t-tests were conducted to evaluate the relationship between therapy duration and rehabilitation outcomes. Results: The findings demonstrated strong positive correlations between therapy duration and functional independence (r = 0.60, p < 0.01), as well as strong negative correlations with pain (r = -0.55, p < 0.01) and depression levels (r = -0.65, p < 0.01). These results suggest that longer therapy duration significantly improves physical functioning, reduces pain, and alleviates depressive symptoms in individuals recovering from SUDs. Conclusion: The study highlights the critical role of extended physical and occupational therapy interventions in SUD rehabilitation. A holistic approach integrating psychosocial support, mental health counseling, and structured therapy programs can enhance recovery outcomes. Future research should focus on multidisciplinary rehabilitation models to optimise treatment effectiveness for individuals with substance use disorders.